Laboratory‐wide association study of survival with prostate cancer. Issue 7 (25th November 2020) - Sohlberg, Ericka M.; Thomas, I‐Chun; Yang, Jaden; Kapphahn, Kristopher; Velaer, Kyla N.; Goldstein, Mary K.; Wagner, Todd H.; Chertow, Glenn M.; Brooks, James D.; Patel, Chirag J.; Desai, Manisha; Leppert, John T.
Abstract : Background: Estimates of overall patient health are essential to inform treatment decisions for patients diagnosed with cancer. The authors applied XWAS methods, herein referred to as "laboratory‐wide association study (LWAS)", to evaluate associations between routinely collected laboratory tests and survival in veterans with prostate cancer. Methods: The authors identified 133, 878 patients who were diagnosed with prostate cancer between 2000 and 2013 in the Veterans Health Administration using any laboratory tests collected within 6 months of diagnosis (3, 345, 083 results). Using the LWAS framework, the false‐discovery rate was used to test the association between multiple laboratory tests and survival, and these results were validated using training, testing, and validation cohorts. Results: A total of 31 laboratory tests associated with survival met stringent LWAS criteria. LWAS confirmed markers of prostate cancer biology (prostate‐specific antigen: hazard ratio [HR], 1.07 [95% confidence interval (95% CI), 1.06‐1.08]; and alkaline phosphatase: HR, 1.22 [95% CI, 1.20‐1.24]) as well laboratory tests of general health (eg, serum albumin: HR, 0.78 [95% CI, 0.76‐0.80]; and creatinine: HR, 1.05 [95% CI, 1.03‐1.07]) and inflammation (leukocyte count: HR, 1.23 [95% CI, 1.98‐1.26]; and erythrocyte sedimentation rate: HR, 1.33 [95% CI, 1.09‐1.61]). In addition, the authors derived and validated separate models for patients with localized and advanced disease, identifying 28 laboratory markers and 15 laboratory markers, respectively, in each cohort. Conclusions: The authors identified routinely collected laboratory data associated with survival for patients with prostate cancer using LWAS methodologies, including markers of prostate cancer biology, overall health, and inflammation. Broadening consideration of determinants of survival beyond those related to cancer itself could help to inform the design of clinical trials and aid in shared decision making. Lay Summary: This article examined routine laboratory tests associated with survival among veterans with prostate cancer. Using laboratory‐wide association studies, the authors identified 31 laboratory tests associated with survival that can be used to inform the design of clinical trials and aid patients in shared decision making. Abstract : The current study identifies common clinical laboratory tests that are associated with mortality in patients with prostate cancer. These tests may aid in the challenging task of estimating life expectancy among men with prostate cancer, among whom overdiagnosis is common and in whom competing risks of mortality dominate prostate cancer–specific mortality risk.